Fibroblast growth factor 21 is induced upon cardiac stress and alters cardiac lipid homeostasis - Manoja K. Brahma (Journal of Lipid Research, 2014)
Fibroblast growth factor 21 (FGF21) is a PPARα-regulated gene elucidated in the liver of PPARα-deficient mice or PPARα agonist-treated mice. Mice globally lacking adipose triglyceride lipase (ATGL) exhibit a marked defect in TG catabolism associated with impaired PPARα-activated gene expression in the heart and liver, including a drastic reduction in hepatic FGF21 mRNA expression. Here we show that FGF21 mRNA expression is markedly increased in the heart of ATGL-deficient mice accompanied by elevated expression of endoplasmic reticulum (ER) stress markers, which can be reversed by reconstitution of ATGL expression in cardiac muscle. In line with this assumption, the induction of ER stress increases FGF21 mRNA expression in H9C2 cardiomyotubes. Cardiac FGF21 expression was also induced upon fasting of healthy mice, implicating a role of FGF21 in cardiac energy metabolism. To address this question, we generated and characterized mice with cardiac-specific overexpression of FGF21 (CM-Fgf21). FGF21 was efficiently secreted from cardiomyocytes of CM-Fgf21 mice, which moderately affected cardiac TG homeostasis, indicating a role for FGF21 in cardiac energy metabolism. Together, our results show that FGF21 expression is activated upon cardiac ER stress linked to defective lipolysis and that a persistent increase in circulating FGF21 levels interferes with cardiac and whole body energy homeostasis.